Musical sensitivity, creativity, and sociability in the play and dance movement of Ilonggo children music education possibilities - Cartagena, Hermie F (University of the Philippines, 2018)
This ethnographic case study aims to find how musical sensitivity, creativity and sociability is developed through dance and play activities. The study also seeks to find the implications of dance and play for classroom music education. The study was done from February-October 2018 at Mandurriao Elementary school, Mandurriao, Iloilo City, involving six (6) children who are considered by their teachers s musically sensitive and creative individuals. A priori inductive (sorting and cutting, similarities and differences, finding related theories) and deductive (indigenous typologies) methods were used in thematic analysis. Triangulation was administered to find the themes and to ensure the reliability of the study. Themes were further validated by three (3) researchers in the field. The findings revealed that dance and ply activities promotes children's musical sensitivity andcreativity as influenced by Dance Activities and Play include (1) personal interest, preferences, and imagination, (2) dance trainings and experiences, (3)socio-cultural experiences, and (4)technological accessibility, implication for music education includes (1) academic learning through dance and play, (2) dance and play as a holistic approach, (3 ) learning motivationthrough dance and play, (4) dance and play as a self-concept builder (5) dance and play for critical and creative thinking, and (6) dance and paly in developing social and self-regulatoryskills. The general recommendation of the study is to provide children with the opportunity to engage in dance and play activities outside and inside the classroom that will promote theirmusical sensitivity and creativity. Also, part of the recommendation is to develop a module using dance and play activities in the classroom. This study was conducted for the aim to improve music education in the country using local and contextual movement strategies, dance and play.